THE SERUM PROTEIN FRACTIONS IN THYMOQUINONE TREATED RATS - Güllü, A; Dede, S (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: TQ has been used as treatment and preventive agent for many diseases over the years. The goal of this study was to investigate the effects of TQ supplement on fractions of serum proteins. Materials and methods: Fourteen male Wistar-Albino rats (200-250 g weight) were used as material for two groups; (control (C) and thymoquinone (TQ) respectively. Each group contained seven rats. The control group had only corn oil, while the TQ group was dissolved in corn oil. 30 mg/kg/day were given by oral gavage for four weeks. The serum protein fractions were identified using cellulose acetate technique. Results: The total protein level and albumin, α-1, α-2 fractions and A/G ratio have showed no difference between groups (p>0.05). β-globulin fractions of TQ group were higher than control’s (p<0.05). In addition, it was observed that the γ-globulin levels of TQ group were lower than that of the control group’s (p<0.05). Conclusion: From the results, it was observed that the changes of these fractions may have originated from elevation or decline synthesis, or activities of containing proteins.